Interaction and main effects of finance support and other business support services on the entrepreneurial ecosystem: A case study of the Mpumalanga Province, South Africa - Ogujiuba Kanayo; Maria Eggink; Ebenezer Gbenga Olamide (Economies, 2023)
Finance support and other forms of business support have been recognized as key factors in the entrepreneurial ecosystem in theoretical and empirical investigations. There is currently a knowledge gap regarding the combined impact of these two variables on the entrepreneurial ecosystem, even though much research has shown that both variables have a favorable influence on entrepreneurial ecosystems. The primary goal of this study is to determine whether the interactions between the two variables-finance support and other business support services-have an impact on the entrepreneurial ecosystem in South Africa. A second objective is to determine the main effects of these variables on the entrepreneurial ecosystem. A standardized questionnaire was used to conduct a study of 2000 SMEs in the South African province of Mpumalanga. To investigate the effects of business support services and finance on the ecosystem as measured by the test instruments, a two-way between-groups analysis of variance was carried out. Depending on their finance index, subjects were classified into three groups: low, medium, and high. There was a statistically significant main effect for finance and other business support services with F(2, 1478) = 26.109, p ≤ 0.001 and F(2, 1478) = 149.552, p ≤ 0.001 respectively. However, the effect sizes were small (partial eta squared = 0.034 and 0.168). Post hoc comparisons using the Tukey HSD test indicated that the mean scores differed for all the groups in finance support and other business support services. It was found that financial support and other business support would impact the SME ecosystem in South Africa positively if implemented separately but not if implemented interactively. The targets of financial support should be separated from other business support during policy formulation and implementation by the government.
Keywords: 330; business support; entrepreneurial ecosystems; finance; SME